Epilobium obscurum Schreb., new species in the flora of Slovenia - Simona Strgulc Krajšek; Nejc Jogan (Natura Sloveniae)
During the revision of herbarium material (Herbarium LJU) of the genus Epilobium , a new species for the flora of Slovenia was found. The specimen of Epilobium obscurum (short-fruited willowherb) had been collected in 1994 in the Koroška (N Slovenia) region. Eventually, some additional localities of this species in the Pohorje Mts. and in the Štajerska (NE Slovenia) region were recorded. The present article deals with known distribution of the species in Slovenia and its most reliable distinguishing characters.